Governing global challenges through quantified futures - Berten, John; Kranke, Matthias (2024)
Abstract: Many contemporary efforts to govern global challenges are driven by combinations of numbers and futures. This special section proposes the novel concept of ‘quantified futures’ as a way of grasping this widespread entanglement. Because existing scholarship has largely treated quantification and futurisation as discrete governing technologies, their intersections have remained undertheorised and underexplored. In this introductory article, we discuss similarities between quantification and futurisation to build an integrated analytical framework that outlines how quantified futures operate across transnational policy domains by shaping the salience, scope and urgency of global challenges and their solutions. The special section at large cautions against overly optimistic expectations regarding the capacity of quantified futures to tackle global challenges. Rather, it underscores the need to enquire into the mutually reinforcing effects between, on the one hand, the growing use of quantified futures and, on the other hand, the increase and diversification of global challenges